Marine cargo insurance - Dunt, John (Lloyd's shipping law library, 2016)
Written by an author who was closely involved with the revisions to the Institute Cargo Clauses 2009, the work expertly examines marine cargo insurance by reference to important English and foreign legal cases as well as the Marine Insurance Act 1906. Logically arranged to reflect the structure of the Institute Cargo Clauses, the most widely used standard form of cover, this text offers easy to find solutions for today's busy practitioner.